Next steps for AWARD - Kamau Rutenberg, Anjiru (African Women in Agricultural Research and Development, 2017)
The purpose of the Diversity and Inclusion Conference is to draw attention to the areas where there is still room for improvement with respect to (gender) diversity and inclusion, and to find ways together to work on these improvements both in research and in the workplace. February 2017